PEMBAGIAN HARTA BERSAMA SETELAH PERCERAIAN (Studi Banding Hukum di Indonesia dengan Malaysia, Jepang, Australia dan Maroko) - Beni Arya Dwinanto (Journal of Innovation Research and Knowledge, 2024)
Community property is property that is formed during the marriage between husband and wife until the marriage bond is broken, except for property obtained by inheritance or a gift from one of the parties. How positive law in Indonesia looks at the legal arrangements for joint property after a divorce then compares with the legal arrangements in force in Malaysia, Japan, Australia and Morocco. The research method used in the research is a type of normative research using literature study and using a comparative study approach. The regulation of joint property in Indonesia can be seen in the Civil Code, Marriage Law and Islamic Law Compilations. In Indonesia, the basic rule for dividing joint assets is ½: ½, whereas in Malaysia the arrangement for dividing joint assets separates the personal acquisitions of each husband and wife as personal property and property obtained "together" or through the efforts and cooperation of the husband and wife. become joint property. Furthermore, in Japan, the division of joint property follows the separation of assets, only property whose ownership status is unclear is designated as joint property. In principle, Australia adheres to a system of separation of property, but the court can consider each person's contribution during the marriage and consider each other's financial needs in the future. Whereas in Morocco, in the division of joint property based on dustur qadim, after a divorce, all assets fall to the wife except vehicles and immovable assets in the name of the husband, this too except the house, whereas in dustur Jadid, everything falls to the wife except the immovable assets above. husband's name includes house